A preparation method and application of silicon carbide porous ceramic material

Silicon carbide porous ceramic materials are prepared through ultrasonic dispersion and multi-step processing, which solves the problems of material defects and process complexity in traditional processes, and achieves improvement in material performance and simplification of the process.

CN118930312BActive Publication Date: 2025-01-21ZHONGKE ZHUOYI GREENE TECH (DONGGUAN) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411205748.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-21
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The silicon carbide porous ceramic materials prepared by the traditional slurry hanging method have surface defects and hollow pore tendons, which affect their mechanical properties, and the high-temperature sintering process is complex, which is not conducive to industrial production.

Method used

Silicon carbide porous ceramic materials are prepared by mixing silicon carbide with porogen, followed by ultrasonic dispersion, press molding, pre-sintering, boiling treatment, sintering and nitriding to control pore distribution and improve thermal conductivity.

Benefits of technology

The mechanical properties of silicon carbide porous ceramic materials are improved, the thermal conductivity is significantly improved, and the process flow is simplified, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005018965600000121
    Figure BDA0005018965600000121
  • Figure BDA0005018965600000122
    Figure BDA0005018965600000122
  • Figure BDA0005018965600000131
    Figure BDA0005018965600000131
Patent Text Reader

Abstract

The invention provides a preparation method and application of a silicon carbide porous ceramic material, and relates to the technical field of silicon carbide fiber composite materials. The preparation method provided by the invention comprises mixing silicon carbide and a porogen, ultrasonically dispersing the mixture in deionized water, and then filtering and drying to obtain a mixed powder; pressing the mixed powder at 300-400MPa to obtain a ceramic matrix; pre-sintering the ceramic matrix at 800-900°C and then cooling to obtain a porous matrix; pressurizing and boiling the porous matrix in deionized water for 1-2h and then cooling to obtain a porous intermediate; sintering the porous intermediate in an inert atmosphere at 1300-1400°C and then cooling to obtain a ceramic intermediate; spreading boron oxide powder on the upper surface of the ceramic intermediate, heating to 450-500°C and keeping the temperature for 2-3h, and then centrifuging to obtain a ceramic composite; nitriding the ceramic composite at 1400-1600°C in a nitrogen atmosphere and then cooling to obtain a silicon carbide porous ceramic material. The present invention can regulate the pore distribution in the porous ceramic material by using a porogen, and can significantly improve the thermal conductivity after adding boron nitride for compounding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicon carbide fiber composite materials, and in particular to a preparation method of a silicon carbide porous ceramic material and application thereof. Background Art

[0002] Porous medium combustion (PMC) uses gas fuel and oxidant to burn in the pores of porous media, mainly using high-temperature solid radiation as the main heat transfer method. It is known as the latest generation of combustion technology in the 21st century. The combustible gas generates vortices, splits and merges in the tiny cavities of the porous medium material, and the gas medium is violently disturbed, forming countless small flames, so that the gas can be fully burned. The heat generated by the combustion is continuously transferred upstream and downstream through the thermal conductivity and radiation effects of the porous medium, so that the temperature distribution of the combustion zone of the entire porous medium is uniform. At the same time, the heat storage capacity of the porous medium itself is used to recover the waste heat of the high-temperature flue gas generated by the combustion.

[0003] Compared with free flame combustion, porous media combustion technology has the advantages of high combustion rate, good stability, uniform heat evolution, and no local high temperature. At the same time, since the combustion takes place in the pores of the porous medium, it can greatly reduce the generation and emission of pollutants such as nitrogen oxides and carbon monoxide. It also has the advantages of high energy density, large composite adjustment range, and high thermal efficiency. It can greatly improve the defects of traditional free flame combustion method such as uneven temperature distribution, incomplete combustion, and high energy consumption.

[0004] The high temperature resistance, thermal conductivity, mechanical properties, corrosion resistance, thermal shock resistance and service life of porous media materials are mainly restricted by the properties of the material itself and the porous media molding method. For example, the pore uniformity after porous molding is poor, which will produce combustion thermal stress during the combustion process and affect the combustion quality, and even tempering may occur, thus affecting the service life of the porous media material. Silicon carbide porous materials have become high-quality materials for high-temperature porous media combustion due to their low thermal expansion coefficient, high thermal conductivity and good thermal shock resistance.

[0005] However, the silicon carbide porous ceramics prepared by the traditional slurry method have a large number of surface defects and hollow pores formed in the porous ceramics due to the high-temperature decomposition of the template skeleton, which seriously affects the mechanical properties of the silicon carbide porous ceramics. In order to improve this defect, the existing technology improves the traditional method, such as adding silicon dioxide and polycarbosilane to silicon carbide powder, and making high-strength silicon carbide porous ceramics after dry pressing and sintering. However, this requires sintering at a high temperature of more than 2200°C, and the process is relatively complicated and not conducive to large-scale industrial production; or silicon powder, alumina powder and aluminum sol can be added to the silicon carbide slurry, and the silicon carbide porous carrier is prepared by organic foam impregnation method. However, this method is difficult to control the coarseness and porosity of the silicon carbide skeleton, and it is easy to cause pore blockage and reduce pore connectivity. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a silicon carbide porous ceramic material and its application. The pore distribution in the porous ceramic material can be regulated by using a porogen, and the thermal conductivity can be significantly improved after adding boron nitride to the composite.

[0007] In a first aspect, the present invention provides a method for preparing a porous silicon carbide ceramic material, comprising the following steps:

[0008] The silicon carbide and the porogen are mixed and dispersed in deionized water by ultrasonication, and then filtered and dried to obtain a mixed powder;

[0009] The mixed powder is pressed at 300-400 MPa to obtain a ceramic matrix;

[0010] The ceramic matrix is ​​pre-sintered at 800-900°C and then cooled to obtain a porous matrix;

[0011] The porous substrate is boiled under pressure in deionized water for 1-2 hours and then cooled to obtain a porous intermediate;

[0012] The porous intermediate is sintered at 1300-1400° C. in an inert atmosphere and then cooled to obtain a ceramic intermediate;

[0013] Spread boron oxide powder on the surface of the ceramic intermediate, heat to 450-500°C, keep warm for 2-3 hours, and then centrifuge to obtain a ceramic composite;

[0014] The ceramic composite is nitrided at 1400-1600° C. in a nitrogen atmosphere and then cooled to obtain a silicon carbide porous ceramic material;

[0015] The preparation method of the porogen comprises: activating carbon nanotubes to obtain activated carbon nanotubes, ultrasonically dispersing the activated carbon nanotubes in a sodium chloride solution to obtain a mixed dispersion; dissolving the mixed dispersion with calcium nitrate to obtain a composite dispersion, and dropwise adding a potassium carbonate solution into the composite dispersion; and filtering, washing and drying after the addition is completed to obtain the porogen.

[0016] The preparation method provided by the present invention can effectively utilize the high-frequency vibration and cavitation effect generated by ultrasonic treatment to evenly disperse the silicon carbide and the porogen, effectively prevent the silicon carbide and the porogen from agglomerating. At the same time, the ultrasonic treatment can also clean the surface of the silicon carbide and the porogen, effectively improve the purity of the product, and enhance the contact and bonding force between the particles. During the pressing and molding, the particles in the mixed powder can be closely arranged, the contact area can be increased, and the mixture can be more compacted. At the same time, the mixed powder can be pressed into a ceramic matrix of a predetermined shape, which is beneficial to subsequent processing and application. During the pre-sintering, the particles in the ceramic matrix can be adhered to each other, and the matrix can be initially solidified, which is beneficial to improving the mechanical strength of the matrix. At the same time, the calcium carbonate in the porogen begins to decompose and form a pore structure in the matrix. During the pressurized boiling process, the porogen can be The residual sodium chloride in the porous intermediate is dissolved and removed, thereby removing the porogen through a two-step method, which can effectively regulate the pore structure and pore distribution in the porous intermediate; at the same time, during high-temperature sintering, the original pore structure in the porous intermediate is rearranged and shrunk again, thereby forming a more refined and uniform pore structure, and promoting the solid-phase sintering reaction between the particles, thereby improving the mechanical strength of the ceramic intermediate; and when the boron oxide powder is spread and heated, the boron oxide powder melts and penetrates into the surface pores of the ceramic intermediate, thereby improving the density and surface strength of the ceramic intermediate, and at the same time, centrifugation can remove excess molten boron oxide, thereby ensuring the integrity of the internal pore structure, and after nitriding, a dense boron nitride network is formed in the ceramic composite, which can not only improve the thermal conductivity of the porous ceramic material, but also enhance the overall density and chemical stability of the material, and has better durability in a high temperature environment.

[0017] Optionally, the carbon nanotubes are activated, including: mixing the carbon nanotubes and a modifier and dispersing them in an activation solution, subjecting the carbon nanotubes to an ultrasonic reaction for 5-8 hours, and then filtering, washing, and drying to obtain activated carbon nanotubes; wherein the modifier includes at least one of polyvinyl pyrrolidone, sodium tripolyphosphate, and sodium polyacrylate, and the solute of the activation solution includes at least one of sodium dodecylbenzene sulfonate, Tween-80, and hexadecyltrimethylammonium bromide.

[0018] Optionally, when ultrasonically dispersing the activated carbon nanotubes in a sodium chloride solution to obtain a mixed dispersion, the method includes: mixing the activated carbon nanotubes in a saturated sodium chloride solution at 80-85° C., ultrasonically mixing, cooling the temperature to 60-65° C. at a rate of 1° C. / min, and then keeping the temperature to obtain a mixed dispersion.

[0019] Optionally, when the activated carbon nanotubes are mixed in a saturated sodium chloride solution at 80-85° C., the mass mixing ratio of the activated carbon nanotubes to the sodium chloride in the saturated sodium chloride solution is 1:(3-4).

[0020] Optionally, after the mixed dispersion liquid and calcium nitrate are mixed and dissolved to obtain a composite dispersion liquid, the mass mixing ratio of the activated carbon nanotubes to the calcium nitrate is 1:(1-2), and the calcium nitrate in the composite dispersion liquid is a saturated dissolved amount.

[0021] Optionally, when the potassium carbonate solution is added dropwise into the composite dispersion, the temperature is gradually lowered to 20-25°C at a rate of 0.5-0.8°C / min, and the mass mixing ratio of the activated carbon nanotubes to the total amount of potassium carbonate added dropwise is 1:(0.1-0.2).

[0022] Optionally, when spreading boron oxide powder on the upper surface of the ceramic intermediate, the mass mixing ratio of the ceramic intermediate to the boron oxide powder is 1:(1-1.5), and the pressure environment on the upper surface of the ceramic intermediate is greater than that on the lower surface, and the pressure difference between the upper surface and the lower surface is 0.1-0.2MPa.

[0023] Optionally, the process of nitriding the ceramic composite in a nitrogen atmosphere at 1400-1600° C. includes: in a nitrogen atmosphere, heating the ceramic composite to 1400-1600° C. at a rate of 5-10° C. / min, and maintaining the temperature for 1-3 hours for nitridation.

[0024] Optionally, the mass mixing ratio of the silicon carbide to the porogen is 1:(0.3-0.5); and / or, the average particle size of the silicon carbide is 5-10 μm; and / or, the solid-liquid ratio after ultrasonic dispersion in deionized water is 0.05-0.08 g / mL.

[0025] In a second aspect, the present invention further provides an application of a silicon carbide porous ceramic material prepared by any of the above optional preparation methods, wherein the application includes a porous medium burner. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0027] The present invention provides a method for preparing a silicon carbide porous ceramic, comprising the following steps:

[0028] S1. Mix silicon carbide and a porogen, disperse them in deionized water by ultrasonic, and then filter and dry to obtain a mixed powder;

[0029] S2, pressing the mixed powder at 300-400 MPa to obtain a ceramic matrix;

[0030] S3, pre-sintering the ceramic substrate at 800-900° C. and then cooling the ceramic substrate to obtain a porous substrate;

[0031] S4, boiling the porous substrate in deionized water under pressure for 1-2 hours and then cooling it to obtain a porous intermediate;

[0032] S5, sintering the porous intermediate at 1300-1400° C. in an inert atmosphere and then cooling to obtain a ceramic intermediate;

[0033] S6. Spread boron oxide powder on the upper surface of the ceramic intermediate, heat to 450-500° C., keep warm for 2-3 hours, and then centrifuge to obtain a ceramic composite;

[0034] S7. Nitriding the ceramic composite in a nitrogen atmosphere at 1400-1600° C. and then cooling the ceramic composite to obtain a silicon carbide porous ceramic material.

[0035] Specifically, the method for preparing the porogen used in step S1 comprises the following steps:

[0036] D1, activating the carbon nanotubes to obtain activated carbon nanotubes;

[0037] D2, ultrasonically dispersing the activated carbon nanotubes in a sodium chloride solution to prepare a mixed dispersion;

[0038] D3. The mixed dispersion liquid is mixed and dissolved with calcium nitrate to obtain a composite dispersion liquid, and the potassium carbonate solution is added dropwise to the composite dispersion liquid. After the addition is completed, the porogen is filtered, washed, and dried to obtain the porogen.

[0039] In some embodiments, the carbon nanotubes used in step D1 may be at least one of multi-walled carbon nanotubes and single-walled carbon nanotubes. Specifically, the carbon nanotubes may be conventional products with a commercial purity of more than 98%.

[0040] In some embodiments, when performing step D1, the steps include: mixing carbon nanotubes and a modifier and dispersing them in an activation solution, and then ultrasonically reacting them for 5-8 hours, followed by suction filtration, washing, and drying to obtain activated carbon nanotubes. Specifically, the modifier used includes at least one of polyvinyl pyrrolidone, sodium tripolyphosphate, and sodium polyacrylate, and the solute of the activation solution includes at least one of sodium dodecylbenzene sulfonate, Tween-80, and hexadecyltrimethylammonium bromide.

[0041] In some embodiments, when performing step D2, the steps include: mixing the activated carbon nanotubes with a saturated sodium chloride solution at 80-85°C, ultrasonically mixing, cooling to 60-65°C at a rate of 1°C / min, and then keeping the temperature to obtain a mixed dispersion. In fact, by cooling during the ultrasonic mixing process, part of the sodium chloride can be gradually precipitated and grown on the surface of the activated carbon nanotubes, which is conducive to forming a sodium chloride modified structure on the surface of the activated carbon nanotubes.

[0042] In some embodiments, when performing step D2, the temperature of the saturated sodium chloride solution is 80-85° C., and the mass mixing ratio of the activated carbon nanotubes to the sodium chloride in the saturated sodium chloride solution is 1:(3-4).

[0043] In some embodiments, when performing step D3, after the mixed dispersion liquid and calcium nitrate are mixed and dissolved to obtain a composite dispersion liquid, the mass mixing ratio of activated carbon nanotubes to calcium nitrate is 1:(1-2), and the calcium nitrate in the composite dispersion liquid is a saturated solubility. Specifically, when the mixed dispersion liquid and calcium nitrate are mixed and dissolved, calcium nitrate powder with a purity of more than 99% can be dissolved in the mixed dispersion liquid, or the calcium nitrate solution and the mixed dispersion liquid are pre-mixed, and then the calcium nitrate powder is added to reach a saturated solubility.

[0044] In some embodiments, when the potassium carbonate solution is added dropwise to the composite dispersion in step D3, the temperature is gradually lowered to 20-25°C at a rate of 0.5-0.8°C / min, and the mass mixing ratio of the activated carbon nanotubes to the total amount of potassium carbonate added dropwise is 1:(0.1-0.2). In this way, during the gradual precipitation of sodium chloride, calcium carbonate can be generated by in-situ reaction on the surface of the activated carbon nanotubes, and a composite structure of sodium chloride and calcium carbonate is formed, thereby making the sodium chloride and calcium carbonate evenly distributed at the nanoscale.

[0045] In some embodiments, when the boron oxide powder is spread on the upper surface of the ceramic intermediate in step S6, the mass mixing ratio of the ceramic intermediate to the boron oxide powder is 1:(1-1.5), the pressure environment on the upper surface of the ceramic intermediate is greater than the pressure environment on the lower surface, and the pressure difference between the upper surface and the lower surface is 0.1-0.2 MPa. This is conducive to the boron oxide powder to melt and penetrate into the ceramic intermediate due to gravity and pressure difference, and the excess boron oxide melt can be removed, thereby blocking the internal pore structure.

[0046] In some embodiments, when executing step S1, the mass mixing ratio of silicon carbide to the porogen is 1:(0.3-0.5), specifically, the average particle size of silicon carbide is 5-10 μm, and the solid-liquid ratio of silicon carbide and the porogen when ultrasonically dispersed in deionized water is 0.05-0.08 g / mL.

[0047] In some embodiments, the process of performing step S7 of nitriding the ceramic composite in a nitrogen atmosphere at 1400-1600° C. includes: heating the ceramic composite to 1400-1600° C. at 5-10° C. / min in a nitrogen atmosphere and maintaining the temperature for 1-3 hours for nitridation.

[0048] Preparation Example 1

[0049] This preparation example 1 provides a method for preparing a porogen, comprising the following steps:

[0050] D1. After mixing multi-walled carbon nanotubes (purchased from Dazhan Nano (Guangdong) Co., Ltd., product name: 99% multi-walled carbon nanotubes) and polyvinyl pyrrolidone (CAS: 9003-39-8, purchased from Shandong Tengxuan Chemical Technology Co., Ltd.), the precursor solution was prepared by dispersing them in an ethanol solution dissolved with Tween-80 (purchased from Tianjin Zhonglian Chemical Reagent Co., Ltd.) at a solid-liquid ratio of 0.1 g / mL. The precursor solution was ultrasonically reacted for 6 hours and then filtered, and washed three times with anhydrous ethanol, and then transferred to a 50°C drying oven and dried until the mass did not change, thereby obtaining activated carbon nanotubes; wherein the mass mixing ratio of multi-walled carbon nanotubes, polyvinyl pyrrolidone, and Tween-80 was 10:1:0.2;

[0051] D2, putting the activated carbon nanotubes into a saturated aqueous solution of sodium chloride at 85°C, performing ultrasonic mixing at a frequency of 20KHz, cooling to 65°C at a rate of 1°C / min, and keeping the temperature for 1 hour to obtain a mixed dispersion; wherein the mass mixing ratio of the activated carbon nanotubes to the sodium chloride in the saturated aqueous solution of sodium chloride at 85°C is 1:3.5;

[0052] D3. The mixed dispersion was mixed with an aqueous solution of calcium nitrate to obtain a composite dispersion, and calcium nitrate was further added to the composite dispersion to reach the saturated solubility of calcium nitrate. A saturated aqueous solution of potassium carbonate was added dropwise to the composite dispersion at a dropping rate of 15 drops / min. During the dropping process, the system temperature was gradually cooled to 25°C at a rate of 0.5°C / min. After ultrasonication and insulation for 2 hours, the dropping was terminated. After filtration, it was washed three times with deionized water, and then transferred to a 50°C vacuum drying oven for drying until the mass did not change, thereby obtaining a porogen. The mass mixing ratio of activated carbon nanotubes, calcium nitrate and potassium carbonate was 1:2:0.2.

[0053] Preparation Example 2

[0054] This Preparation Example 2 provides a preparation method for a porogen, which is different from Preparation Example 1 in that step D3 is not performed, and the mixed dispersion prepared in step D2 is filtered and transferred to a 50°C drying oven to be dried until the mass does not change, and then mixed with calcium carbonate powder with a particle size of 50-100 μm (purchased from Tianjin Zhonglian Chemical Reagent Co., Ltd.) at a mass ratio of 1:0.3 to obtain a porogen.

[0055] Preparation Example 3

[0056] Preparation Example 3 provides a preparation method of a porogen, which is different from Preparation Example 1 in that step D2 is not performed, and in step D3, the activated carbon nanotubes are mixed with a calcium nitrate aqueous solution to obtain a composite dispersion, and calcium nitrate is further added to the composite dispersion to reach the saturated solubility of calcium nitrate, and a saturated potassium carbonate aqueous solution is added dropwise to the composite dispersion, and the dropping rate is controlled to be 15 drops / min. During the dropping process, the system temperature is gradually cooled to 25°C at a rate of 0.5°C / min, and the dropping is terminated after ultrasonication and insulation for 2 hours. After filtration, the mixture is washed three times with deionized water, transferred to a 50°C vacuum drying oven, and dried until the mass does not change, and then mixed with sodium chloride powder with a particle size of 100-200 μm (purchased from Tianjin Zhonglian Chemical Reagent Co., Ltd.) at a mass ratio of 1:0.3 to obtain a porogen; wherein the mass mixing ratio of the activated carbon nanotubes, calcium nitrate, and potassium carbonate is 1:2:0.2.

[0057] Preparation Example 4

[0058] This Preparation Example 4 provides a method for preparing a porogen, comprising the following steps: multi-walled carbon nanotubes, sodium chloride powder with a particle size of 100-200 μm, and calcium carbonate powder with a particle size of 50-100 μm are mixed and ground in a mass ratio of 1:0.2:0.2 to obtain a porogen.

[0059] Example 1

[0060] This embodiment 1 provides a method for preparing a silicon carbide porous ceramic material, comprising the following steps:

[0061] S1. Silicon carbide powder with an average particle size of 5 μm (purchased from Guangzhou Metal Metallurgy (Group) Co., Ltd.) was mixed with the porogen prepared in Preparation Example 1 at a mass ratio of 1:0.4, added with deionized water at a solid-liquid ratio of 0.08 g / mL, and ultrasonically treated at a frequency of 20 kHz for 2 h, filtered, rinsed with anhydrous ethanol, and transferred to a 70° C. drying oven for 1 h to obtain a mixed powder;

[0062] S2, pressing the mixed powder under a mechanical pressure of 350 MPa to obtain a ceramic matrix;

[0063] S3, placing the ceramic substrate in an atmosphere furnace, heating it to 850°C at a rate of 5°C / min in an air atmosphere, calcining it for 3 hours, and then cooling it to room temperature to obtain a porous substrate;

[0064] S4, putting the porous matrix into deionized water at a solid-liquid ratio of 0.06 g / mL, heating to 120°C under 2 standard atmospheric pressures and boiling for 2 hours, taking out the porous matrix and rinsing it with deionized water at 90°C, cooling it to room temperature and drying it in a drying oven at 50°C until the mass does not change, to obtain a porous intermediate;

[0065] S5, placing the porous intermediate in a graphite ark, heating the porous intermediate to 1350° C. at a rate of 5° C. / min in an argon atmosphere, and then maintaining the temperature for 2 h to sinter the porous intermediate, and then cooling the intermediate to room temperature to obtain a ceramic intermediate;

[0066] S6. Fix the ceramic intermediate in an atmosphere furnace, and spread boron oxide powder (average particle size 100 mesh, purchased from Shanghai Yingfeng Ruihuang Metal Co., Ltd.) on the upper surface of the ceramic intermediate, the spreading thickness of the boron oxide powder is 3 mm, and the mass ratio of the ceramic intermediate to the boron oxide powder is 1:1.2; apply different air pressures on the upper and lower surfaces of the ceramic intermediate, and the pressure difference is 0.1 MPa; heat the atmosphere furnace to 460°C and keep it warm for 2.5 hours, and quickly transfer it to a high-temperature centrifugal device, centrifuge it at 460°C at a speed of 200 rpm, and cool it to room temperature to obtain a ceramic composite;

[0067] S7. Place the ceramic composite in a graphite ark and transfer it to an atmosphere furnace. Heat the furnace to 1500°C at a rate of 5°C / min under a nitrogen atmosphere and keep it at that temperature for 2 hours for nitriding treatment. Then cool the furnace to room temperature to obtain a silicon carbide porous ceramic material.

[0068] Comparative Example 1

[0069] This comparative example 1 provides a method for preparing a silicon carbide porous ceramic material, which is different from that of example 1 in that the porogen prepared in preparation example 2 is used in step S1.

[0070] Comparative Example 2

[0071] Comparative Example 2 provides a method for preparing a porous silicon carbide ceramic material, which is different from Example 1 in that the porogen prepared in Preparation Example 3 is used in step S1.

[0072] Comparative Example 3

[0073] This comparative example 3 provides a method for preparing a silicon carbide porous ceramic material, which is different from that of example 1 in that the porogen prepared in preparation example 4 is used in step S1.

[0074] Comparative Example 4

[0075] This comparative example 4 provides a method for preparing a porous silicon carbide ceramic material, which is different from Example 1 in that step S6 and step S7 are not performed, and the ceramic intermediate prepared in step S5 is the porous silicon carbide ceramic material.

[0076] Comparative Example 5

[0077] This comparative example 5 provides a method for preparing a porous silicon carbide ceramic material, which is different from Example 1 in that, in step S6, the ceramic intermediate is immersed in a molten boron oxide melt at 460°C for 2 hours and then taken out, centrifuged at 200 rpm, and then cooled to room temperature to obtain a ceramic composite.

[0078] Performance Testing

[0079] Thermal shock resistance: Based on GB / T 30873-2014 “Test method for thermal shock resistance of refractory materials”, the silicon carbide porous ceramic materials prepared in Example 1 and Comparative Examples 1 to 5 were respectively made into test samples of 230 mm×1140 mm×65 mm. All the test samples were dried to constant weight in an electric drying oven at 110°C, and then transferred to a 1400°C constant temperature heating furnace for 20 min. They were quickly taken out and transferred to 20°C running water, and the temperature rise of the upstream and downstream of the running water was adjusted to be less than or equal to 10°C. After the test samples were cooled to room temperature, the thermal shock test was cyclically performed until the degree of damage on the end face of the test sample exceeded 1 / 2, and the number of cyclic thermal shocks was recorded as shown in Table 1.

[0080] Thermal conductivity: The silicon carbide porous ceramic materials prepared in Example 1 and Comparative Examples 1 to 5 were respectively made into test samples with a diameter of 12.7 mm and a thickness of 2 mm. All the test samples were placed on the sample holder of a laser flash thermal conductivity apparatus. The side of the test sample was instantaneously heated by a laser pulse. The temperature rise curve of the other opposite side of the test sample was measured by an infrared sensor, and the thermal conductivity was calculated as shown in Table 1 below.

[0081] Compressive strength: The silicon carbide porous ceramic materials prepared in Example 1 and Comparative Examples 1 to 5 were respectively made into test samples of 25 mm × 25 mm × 50 mm. A universal testing machine was used to apply a compressive load to all the test samples at a rate of 0.5 mm / min until the test samples were destroyed. The maximum load was recorded and the compressive strength was calculated as shown in Table 1 below.

[0082] Porous properties: The silicon carbide porous ceramic materials prepared in Example 1 and Comparative Examples 1 to 5 were made into 50 mm × 50 mm × 50 mm cubic test samples, and the dry weight W of the test samples was measured. d After that, the samples to be tested were placed in boiling water and boiled for 2 hours, then taken out, cooled to room temperature and the surface moisture was wiped dry, and the wet weight W of the samples to be tested was weighed. s , and then suspend the sample to be tested in water, and record the suspended weight of the sample to be tested. h Based on the following formulas, the apparent porosity P, water absorption A and volume density ρ of the test sample were calculated respectively. The calculation results are shown in Table 2.

[0083]

[0084] Table 1 Thermal shock, thermal conductivity and compression test data

[0085] Thermal shock resistance Thermal conductivity / (W / m·K) Compressive strength / MPa Example 1 36 168.7 43.4 Comparative Example 1 31 160.4 40.5 Comparative Example 2 32 162.1 41.2 Comparative Example 3 29 158.6 39.9 Comparative Example 4 34 146.2 42.3 Comparative Example 5 33 173.8 41.6

[0086] Table 2 Multi-hole detection data

[0087]

[0088]

[0089] It can be seen from Table 1 and Table 2 that since the calcium carbonate and sodium chloride in the porogens used in Comparative Examples 1, 2 and 3 are unevenly distributed at the nanoscale, the pore structure formed is not uniform, resulting in reduced seismic resistance and thermal conductivity. At the same time, due to the uneven pores, the local stress of the silicon carbide material is more concentrated, resulting in a decrease in compressive strength.

[0090] It can be seen from Tables 1 and 2 that due to the lack of boron oxide coating in the porous ceramic of Comparative Example 4, the overall structural performance of the ceramic material is reduced, the compressive performance and thermal shock resistance are reduced, and the thermal conductivity is also greatly reduced, which indicates that the boron nitride network structure in the porous ceramic can significantly improve the thermal conductivity.

[0091] As can be seen from Tables 1 and 2, due to the immersion in the boron oxide melt in Comparative Example 5, too much boron oxide melt enters the ceramic content, resulting in partial pores being closed, which greatly affects the uniformity of the internal pores, and the fluid flow path is reduced, the thermal stress during thermal shock is more concentrated, and the thermal shock resistance and compressive strength are reduced. At the same time, although boron nitride can improve thermal conductivity after sealing the pores, the porosity is greatly reduced and the density is increased.

[0092] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A method for preparing a silicon carbide porous ceramic material, characterized in that: The following steps are involved: The silicon carbide and the porogen are mixed and dispersed in deionized water by ultrasonication, and then filtered and dried to obtain a mixed powder; The mixed powder is pressed at 300-400 MPa to obtain a ceramic matrix; The ceramic matrix is ​​pre-sintered at 800-900°C and then cooled to obtain a porous matrix; The porous substrate is boiled under pressure in deionized water for 1-2 hours and then cooled to obtain a porous intermediate; The porous intermediate is sintered at 1300-1400° C. in an inert atmosphere and then cooled to obtain a ceramic intermediate; Spread boron oxide powder on the surface of the ceramic intermediate, heat to 450-500°C, keep warm for 2-3 hours, and then centrifuge to obtain a ceramic composite; The ceramic composite is nitrided at 1400-1600° C. in a nitrogen atmosphere and then cooled to obtain a silicon carbide porous ceramic material; The preparation method of the porogen comprises: activating carbon nanotubes to obtain activated carbon nanotubes, ultrasonically dispersing the activated carbon nanotubes in a sodium chloride solution to obtain a mixed dispersion; mixing and dissolving the mixed dispersion with calcium nitrate to obtain a composite dispersion, and dropwise adding a potassium carbonate solution into the composite dispersion; and filtering, washing and drying after the addition is completed to obtain the porogen.

2. The preparation method according to claim 1, characterized in that: The activation treatment of carbon nanotubes includes: mixing carbon nanotubes and modifiers and dispersing them in an activation solution, subjecting the carbon nanotubes to ultrasonic reaction for 5-8 hours, and then filtering, washing and drying to obtain activated carbon nanotubes; wherein the modifier includes at least one of polyvinyl pyrrolidone, sodium tripolyphosphate and sodium polyacrylate, and the solute of the activation solution includes at least one of sodium dodecylbenzene sulfonate, Tween-80 and hexadecyltrimethylammonium bromide.

3. The preparation method according to claim 1, characterized in that: When the activated carbon nanotubes are ultrasonically dispersed in a sodium chloride solution to obtain a mixed dispersion, the method includes: mixing the activated carbon nanotubes in a saturated sodium chloride solution at 80-85°C, ultrasonically mixing, cooling to 60-65°C at a rate of 1°C / min, and then keeping warm to obtain a mixed dispersion.

4. The preparation method according to claim 3, characterized in that: When the activated carbon nanotubes are mixed in a saturated sodium chloride solution at 80-85° C., the mass mixing ratio of the activated carbon nanotubes to the sodium chloride in the saturated sodium chloride solution is 1:(3-4).

5. The preparation method according to claim 1, characterized in that: After the mixed dispersion liquid and calcium nitrate are mixed and dissolved to obtain a composite dispersion liquid, the mass mixing ratio of the activated carbon nanotubes to the calcium nitrate is 1:(1-2), and the calcium nitrate in the composite dispersion liquid is a saturated dissolved amount.

6. The preparation method according to claim 1, characterized in that: When boron oxide powder is spread on the upper surface of the ceramic intermediate, the mass mixing ratio of the ceramic intermediate to the boron oxide powder is 1:(1-1.5), the pressure environment on the upper surface of the ceramic intermediate is greater than that on the lower surface, and the pressure difference between the upper surface and the lower surface is 0.1-0.2MPa.

7. The preparation method according to claim 1, characterized in that: The process of nitriding the ceramic composite in a nitrogen atmosphere at 1400-1600° C. includes: in a nitrogen atmosphere, heating the ceramic composite to 1400-1600° C. at a rate of 5-10° C. / min, and keeping the temperature for 1-3 hours for nitridation.

8. The preparation method according to claim 1, characterized in that: The mass ratio of the silicon carbide to the porogen is 1:(0.3-0.5); and / or the average particle size of the silicon carbide is 5-10 μm; and / or the solid-liquid ratio after ultrasonic dispersion in deionized water is 0.05-0.08 g / mL.

9. An application of a silicon carbide porous ceramic material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The applications include porous media burners.

Citation Information

Patent Citations

  • Preparation method of porous ceramic-metal composite film material

    CN102836642A

  • Structure and preparation method of porous silicon nitride ceramic surface coating

    CN113816771A